2019
DOI: 10.1002/adtp.201900114
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Artificial Intelligence to Optimize Long‐Term Maintenance Dosing for Antiretroviral‐Naive Adults with HIV‐1 Infection

Abstract: Antiretroviral therapy (ART) serves as a mainstay in treating human immunodeficiency virus (HIV)infection. An HIV patient is traditionally administered the same ART regimen for life, even if his/her viral load has been reduced by several orders of magnitude from the initial viral load. Dose reduction in ART has been clinically explored in a trial-and-error manner to reduce side effects and improve ART sustainability. Using artificial intelligence (AI), we have discovered that drugs and doses inputs can be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…With the emergence of AI, lots of researchers are taking the help of ML and DL algorithms to determine appropriate drug dosage. For instance, Shen et al [ 122 ] developed an AI-based platform, referred to as AI-PRS, to determine the optimum dose and combinations of drugs to be used for HIV treatment through antiretroviral therapy. AI-PRS is a neural network-driven approach, which relates drug combinations and dosage to efficacy through a parabolic response curve (PRS).…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…With the emergence of AI, lots of researchers are taking the help of ML and DL algorithms to determine appropriate drug dosage. For instance, Shen et al [ 122 ] developed an AI-based platform, referred to as AI-PRS, to determine the optimum dose and combinations of drugs to be used for HIV treatment through antiretroviral therapy. AI-PRS is a neural network-driven approach, which relates drug combinations and dosage to efficacy through a parabolic response curve (PRS).…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…This can be insurmountably challenging when considering the fact that a small pool of 12 drugs with each drug studied at 10 dosing levels results in 1 trillion possible drug combinations. To overcome this testing challenge, we have previously harnessed an artificial intelligence (AI)-driven quadratic relationship between drug/dose inputs and efficacy/safety outputs to markedly reduce the number of prospective assays needed to pinpoint the right drugs and doses with potential to improve treatment outcomes [ [118] , [119] , [120] , [121] , [122] , [123] ]. To this end, the patient’s clinical/laboratorial data (baseline and follow-ups) and therapeutic regime (initial and adjusted doses) are constantly analyzed using computational power like quadratic phenotypic optimization platform.…”
Section: Optimizing Antiviral Delivery With Artificial Intelligencementioning
confidence: 99%
“…Likewise, AI has been used in a pilot study to optimize the dose of antiretroviral drugs for treating HIV infection. The AI platform identified that the tenofovir dose could be reduced for the long-term maintenance regimen with no relapse for 33 months [ 121 ].
Fig.
…”
Section: Optimizing Antiviral Delivery With Artificial Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, positive treatment outcomes were observed in direct ex vivo to clinical validation studies for hematologic cancer (Quadratic Phenotypic Optimization Platform [QPOP]), and the key role of dynamic clinical dosing on efficacy was further validated on an advanced solid cancer patient (CURATE.AI) . In the area of infectious diseases, low‐dose treatment for human immunodeficiency virus (HIV) was shown to mediate undetectable viral loads while opening the doors to possible downstream reductions in treatment complications arising from side effects of high‐dose therapy (CURATE.AI) …”
Section: Accelerating Combination Therapy Development and Optimizatiomentioning
confidence: 99%